Thermally-induced atropisomerism promotes metal-organic cage construction - Jiaqi Liang; Shuai Lu; Yang Yang; Yun-Jia Shen; Jin-Ku Bai; Xin Sun; Xu-Lang Chen; Jie Cui; Ai-Jiao Guan; Jun-Feng Xiang; Xiaopeng Li; Heng Wang; et al. (Nature Communications, 2023)
Abstract Molecular folding regulation with environmental stimuli is critical in living and artificial molecular machine systems. Herein, we described a macrocycle, cyclo[4] (1,3-(4,6-dimethyl)benzene)[4](1,3-(4,6-dimethyl)benzene)(4-pyridine). Under 298 K, it has three stable stiff atropisomers with names as 1 (C s symmetry), 2 (C s symmetry), and 3 (C 4v symmetry). At 393 K, 1 can reversibly transform into 2, but at 473 K, it can irrevocably transform into 3. At 338 K, 3 and (PhCN)2PdCl2 complex to produce the metal-organic cage 4. Only at 338 K does the combination of 1 or 2 and (PhCN)2PdCl2 create a gel-like structure. Heating both gels to 473 K transforms them into 4. In addition to offering a thermally accelerated method for modifying self-assembled systems using macrocyclic building blocks, this study also has the potential to develop the nanoscale transformation material with a thermal response.